Hutchinson-Gilford progeria syndrome complicated with stroke: A report of 2 cases and literature review - Wang, Jingjing; Yu, Qinmei; Ma, Xiaohui; Yuan, Zhefeng; Mao, Jianhua (Frontiers in Pediatrics, 2022)
Background: Hutchinson–Gilford progeria syndrome is a ultrarare, fatal autosomal dominant disorder. The pathogenesis of the disease is a mutation in LMNA, which leads to the accumulation of progerin in cells, impairing the normal physiological functions. Stroke and transient ischemic attack seriously affect the survival rate and quality of life of HGPS children, although t the literature of this aspect is limited. We have summarized the clinical manifestations and the related imaging features of HGPS children with stroke to improve the pediatric clinicians' understanding of this disease. Case presentation: Both children showed a de novo heterozygous mutation of LMNA (c.1824C>T (p.G608G)). Case 1. At the age of 4 years, the child had a cerebral infarction, which manifested as blurred vision and communication disturbance. Multiple abnormal signals were observed on the head MRI in the bilateral frontoparietal cortex, bilateral semiovale center, lateral ventricle, and deep frontal and parietal lobes. Multiple abnormal white matter signals on the head MRA showed bilateral internal carotid artery stenosis with basilar artery and bilateral thickening of the posterior communicating artery. Case 2. At the age of 8.5 years, the child presented with cerebral infarction, which manifested as decreased muscle strength and choking after drinking water. MRI of the child’s head showed that the bilateral frontal lobes were small with multiple abnormal signal shadows in the bilateral center of the semiovale and the lateral ventricle. Brain MRA revealed that the bilateral internal carotid arteries (C5-7) were narrow and non-uniform in thickness, and the A1 segment of the left anterior cerebral artery was narrower than the contralateral one. After symptomatic and supportive treatment, the two children improved. Conclusion: Hemiplegia and physical weakness are the most prevalent stroke symptoms in children with HGPS, followed by headache, epilepsy, dysarthria, and psychosis as the primary manifestation in some children. Stroke in children with HGPS is mostly ischemic cerebral infarction caused by an insufficient cerebral blood supply. Pediatric cerebral infarction mainly occurs in the large vascular area, involving all vascular areas, with the internal carotid artery and middle cerebral artery being the most often involved.